2017
DOI: 10.1128/jvi.00312-17
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor p53 Stimulates the Expression of Epstein-Barr Virus Latent Membrane Protein 1

Abstract: Epstein-Barr virus (EBV) is associated with multiple human malignancies. EBV latent membrane protein 1 (LMP1) is required for the efficient transformation of primary B lymphocytes and possibly The tumor suppressor p53 plays a seminal role in cancer development. In some EBV-associated cancers, p53 tends to be wild type and overly expressed; however, the effects of p53 on LMP1 expression is not clear. We find LMP1 expression to be associated with p53 expression in EBV-transformed cells under physiological and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
2
11
0
Order By: Relevance
“…Tumor protein p53, or simply p53, is closely related to the occurrence of gastric cancer, and many studies find EBV infection to be associated with p53 methylation ( 21 23 ). In 2019, Camargo et al.…”
Section: How To Test Ebv-positive Gastric Cancermentioning
confidence: 99%
“…Tumor protein p53, or simply p53, is closely related to the occurrence of gastric cancer, and many studies find EBV infection to be associated with p53 methylation ( 21 23 ). In 2019, Camargo et al.…”
Section: How To Test Ebv-positive Gastric Cancermentioning
confidence: 99%
“…IRF5 binds cellular DNA to its amino-terminal domain and regulates the transcription of some of the genes involved in inflammation, such as type I IFNs and other cytokines including interleukin-17 (IL-17). Some studies have shown that IRF5 may induce a permissive background to latent viral infections such as those due to EBV and favours the process of B cell transformation into malignant clones [11], whereas others have reported that IRF5 may prevent the development of hepatocellular carcinoma and that this mediator is characteristically downregulated during HCV infection [12]. Both EBV and HCV are associated with SS and may give rise to an aberrant activation of the immune system in genetically predisposed subjects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, AcMNPV P35 can inhibit insect cell and mammalian cell apoptosis [24]. A recent study showed that p53 stimulates the expression of Epstein-Barr virus latent membrane protein 1, which may inhibit p53-induced cell apoptosis [25]. It is unknown whether certain viral proteins of SeV can inhibit p53 signaling.…”
Section: Discussionmentioning
confidence: 99%